Áreas de preservação permanente urbanas e direito à moradia: estudo de caso das Glebas Guamá ii e Palheta do Município de Mãe do Rio - PA - TUMA, Erica Fabiola Brito (2017)
The objective of the dissertation is to analyze the Citizen Housing Land Use Regularization Project highlighting the rights to housing and the balanced environment, in light of socioenvironmental legal principles. Subsequently, the right to housing as a social right, enshrined in the 1988 Constitution and its relation to the right to the environment ecologically balanced. The legislation and doctrine of the Permanent Preservation Urban Areas is analyzed as an instrument of environmental protection. There is verified the current legislation of urban land regularization, and the modifications produced by the recent Provisional Measure n. 759/2016. Finally, in the specific case of the municipality of Mãe do Rio (Pará), through the weighting of principles, the density and relevance of socio-environmental legal principles is verified. The work is developed through bibliographical and documentary research.